A Simplified Approach to Jaw-in-a-Day Using a Preassembled Prosthesis: Lowering the Barrier to Entry - Theodore V. Tso, DMD, MMSc; Nicholas Do, MD; Sohyun S. Park, DMD, MMSc; Briana Burris, DDS; Eric Crum, DDS (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Fibula flap reconstruction with primary dental implant placement has been established as a successful procedure for composite mandibular defects. When using virtual surgical planning, these techniques typically require additional personnel and materials preoperatively and intraoperatively to fabricate occlusal-based guidance and prosthesis. The authors present a technique utilizing a custom-made implant-supported prosthesis completed before surgery that greatly reduces lead time and needed resources. The authors follow the established workflow of segmental mandibulectomy and fibula flap reconstruction using premanufactured cutting guides and placement of dental implants. Cylindrical holes along the implant axes are included in the printed surgical model provided by the guide manufacturer. Acrylic resin and abutments are added to the model to a positioning stent for use during surgery that does not require intraoperative modification before fibula inset. This ensures optimal position for facial esthetics and fixed dental rehabilitation. The presented technique uses printed models already provided by the guide manufacturer, reducing preparation time and requiring fewer personnel and materials intraoperatively. This is an approach to the jaw-in-a-day procedure with a lower barrier to entry that may be used by new craniofacial teams.